2007
DOI: 10.1167/iovs.07-0342
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Glaucoma in a South Brazilian Population: Projeto Glaucoma

Abstract: Compared to incidence in Hispanic and European populations, PACG was more common among South Brazilians, whereas the POAG rates were similar. The rate of undiagnosed glaucoma was almost 90%. The higher POAG prevalence in the population self-reported as nonwhite may affect the estimation of glaucoma in Brazil, as more than 40% of the population self-report their race as nonwhite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
3
24

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(78 citation statements)
references
References 33 publications
5
46
3
24
Order By: Relevance
“…An epidemiological study showed that the prevalence of primary angle-closure glaucoma was much higher in Asia, especially in China, than in other areas. [15][16][17][18] The aim of malignant glaucoma therapy is to relieve the ciliolenticular block, disrupt the misdirection of aqueous humor and to restore normal aqueous flow. 19 Drug therapy induces a posterior movement of the lens-iris diaphragm, reduces the production of aqueous humor, and dehydrates the vitreous volume.…”
Section: Discussionmentioning
confidence: 99%
“…An epidemiological study showed that the prevalence of primary angle-closure glaucoma was much higher in Asia, especially in China, than in other areas. [15][16][17][18] The aim of malignant glaucoma therapy is to relieve the ciliolenticular block, disrupt the misdirection of aqueous humor and to restore normal aqueous flow. 19 Drug therapy induces a posterior movement of the lens-iris diaphragm, reduces the production of aqueous humor, and dehydrates the vitreous volume.…”
Section: Discussionmentioning
confidence: 99%
“…There is some consensus among published papers that the scleral spur is more easily identifiable with AS-OCT, although in our experience there was no difficulty with either method. 12,27 This fact could potentially signify better accuracy for OCT measurements when compared with UBM.…”
Section: Eyementioning
confidence: 99%
“…Direct epidemiologic data on prevalence of CAG in Latin America are limited. They range from a general estimation of 5.7% of glaucoma cases (1) to 21.4% in one sample from South Brazil (30) . Unpublished surveys indicate that CAG rates may be high in some native ethnic populations within Latin America.…”
Section: Discussionmentioning
confidence: 89%